Scheffersomyces spartinae Fungemia among Pediatric Patients, Pakistan, 2020–2024 - Kauser Jabeen; Joveria Farooqi; Lacy M. Simons; Judd F. Hultquist; Ramon Lorenzo-Redondo; Charlesnika T. Evans; Erica M. Hartmann; Mohammad Hanif; Zahra Hasan; Syed Faisal Mahmood; Javaria Ashraf; Hassan Ghayas; et al. (Emerging Infectious Diseases, 2025)
Prevalence of emerging fungal infections is increasing, particularly among immunocompromised persons, children, and older persons. We report 108 cases of Scheffersomyces spartinae infection in pediatric patients from Karachi and other cities in Pakistan, of which 107 were identified from blood cultures. Cultures were initially misidentified as Clavispora lusitaniae by a biochemical assay before speciation as S. spartinae by whole-genome sequencing. All isolates were from children <12 years of age, and >69% were from children <1 month of age. Isolates were genetically distinct across regions of Pakistan; however, genetic diversity was low in isolates from patients in Karachi and nearby Nawabshah and had median differences of just 9 pairwise nucleotide variants. This study demonstrates S. spartinae is a potentially emerging pathogen in neonates and young infants in Pakistan. The findings highlight the limitations of phenotypic identification for detecting emerging fungal infections and underscore the value of molecular identification approaches.